2020
DOI: 10.3390/jdb8040023
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans Apical Extracellular Matrices Shape Epithelia

Abstract: Apical extracellular matrices (aECMs) coat exposed surfaces of epithelia to shape developing tissues and protect them from environmental insults. Despite their widespread importance for human health, aECMs are poorly understood compared to basal and stromal ECMs. The nematode Caenorhabditis elegans contains a variety of distinct aECMs, some of which share many of the same types of components (lipids, lipoproteins, collagens, zona pellucida domain proteins, chondroitin glycosaminoglycans and proteoglycans) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 211 publications
1
61
0
Order By: Relevance
“…The C. elegans epidermis (known as the hypodermis) secretes a complex multilayered aECM beginning in late embryogenesis and thereafter in four molts, resulting in the mature adult cuticle consisting of an outer surface coat, a lipid-rich epicuticle, and the multilayered collagenous cuticle ( Figure 1a ) 6 8 . Other epithelial aECMs in C. elegans include those of internal tubes, such as the excretory duct and vulva, and specialized aECMs of sensory organs 4 , 9 . Recent bioinformatic analysis has enumerated components of the C. elegans ECM (including aECMs), predicting a total “matrisome” of over 700 proteins 10 .…”
Section: Caenorhabditis Elegans Aecm Components and Biosynthmentioning
confidence: 99%
See 1 more Smart Citation
“…The C. elegans epidermis (known as the hypodermis) secretes a complex multilayered aECM beginning in late embryogenesis and thereafter in four molts, resulting in the mature adult cuticle consisting of an outer surface coat, a lipid-rich epicuticle, and the multilayered collagenous cuticle ( Figure 1a ) 6 8 . Other epithelial aECMs in C. elegans include those of internal tubes, such as the excretory duct and vulva, and specialized aECMs of sensory organs 4 , 9 . Recent bioinformatic analysis has enumerated components of the C. elegans ECM (including aECMs), predicting a total “matrisome” of over 700 proteins 10 .…”
Section: Caenorhabditis Elegans Aecm Components and Biosynthmentioning
confidence: 99%
“…External aECMs can incorporate lipid layers that provide desiccation resistance and permeability barrier function. Internal aECMs, such as those of tubular epithelia, often have transient developmental roles in shaping tube morphology 3 , 4 . Other aECMs found in vertebrates include the vascular glycocalyx, the mucin-rich coating of the gastrointestinal tract and upper airways, and the alveolar surfactant of lungs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that RNAi-mediated knockdown of many C. elegans ptr genes led to defects in cuticular structure and molting (Hao et al, 2006a; Zugasti et al, 2005), suggesting a potential role for PTR proteins in trafficking or export of components of the apical extracellular matrix (aECM). C. elegans has multiple distinct types of aECM, including a chitinous eggshell and a collagenous cuticle that must be disassembled and rebuilt during each of four larval molts (Cohen and Sundaram, 2020; Page and Johnstone, 2007; Stein and Golden, 2018). Prior to the generation of each new cuticle, a molecularly distinct aECM, termed the sheath or pre-cuticle, coats external epithelia (Cohen et al, 2020b; Cohen and Sundaram, 2020; Priess and Hirsh, 1986; Vuong-Brender et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…C. elegans has multiple distinct types of aECM, including a chitinous eggshell and a collagenous cuticle that must be disassembled and rebuilt during each of four larval molts (Cohen and Sundaram, 2020; Page and Johnstone, 2007; Stein and Golden, 2018). Prior to the generation of each new cuticle, a molecularly distinct aECM, termed the sheath or pre-cuticle, coats external epithelia (Cohen et al, 2020b; Cohen and Sundaram, 2020; Priess and Hirsh, 1986; Vuong-Brender et al, 2017). Similar to some mammalian aECMs such as lung surfactant (Pérez-Gil, 2008) or eye tear film (Dartt, 2011), all of these C. elegans aECMs appear to contain layers with significant lipid content (Bai et al, 2020; Blaxter, 1993; Dartt, 2011; Forman-Rubinsky et al, 2017; Pu et al, 2017; Schultz and Gumienny, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation